Fuzzy Inverse Compactness - Halis Aygün; A. Arzu Bural; S. R. T. Kudri (International Journal of Mathematics and Mathematical Sciences)
We introduce definitions of fuzzy inverse compactness, fuzzy inverse countable compactness, and fuzzy inverse Lindelöfness on arbitrary 𝐿-fuzzy sets in 𝐿-fuzzy topological spaces. We prove that the proposed definitions are good extensions of the corresponding concepts in ordinary topology and obtain different characterizations of fuzzy inverse compactness.